Validity of project-based teaching module to empower students' environmental caring character - Wily Hartanto; Tarzan Purnomo; Pramita Yakub (JPBI (Jurnal Pendidikan Biologi Indonesia), 2024)
Environmental problems caused by waste and exploitation of natural resources can be exacerbated by a lack of awareness and concern for the environment. One of the contributing factors is the lack of utilization of learning resources and environmental-based media in education. This study aims to develop and validate a teaching module based on the PjBL (Project-based Learning) model to increase students' environmental awareness, especially on the topic of environmental change. By using the 4D Model, this study uses quantitative descriptive analysis involving validation by two experts. The validation values ​​for learning plan, learning media, and students' worksheet were 3.48, 3.52, and 3.45, respectively. The results of the recapitulation of validity data show a total score of 3.48 with a valid category. It was concluded that teaching modules based on project to improve environmental character are worthy of being applied in Biology learning at school.